Mechanisms of FSH- and Amphiregulin-Induced MAP Kinase 3/1 Activation in Pig Cumulus-Oocyte Complexes During Maturation In Vitro - Prochazka, Radek; Nemcova, Lucie (International journal of molecular sciences, 2019)
The maturation of mammalian oocytes in vitro can be stimulated by gonadotropins (follicle-stimulating hormone, FSH) or their intrafollicular mediator, epidermal growth factor (EGF)-like peptide-amphiregulin (AREG). We have shown previously that in pig cumulus-oocyte complexes (COCs), FSH induces expression and the synthesis of AREG that binds to EGF receptor (EGFR) and activates the mitogen-activated protein kinase 3/1 (MAPK3/1) signaling pathway. However, in this study we found that FSH also caused a rapid activation of MAPK3/1 in the cumulus cells, which cannot be explained by the de novo synthesis of AREG. The rapid MAPK3/1 activation required EGFR tyrosine kinase (TK) activity, was sensitive to SRC proto-oncogene non-receptor tyrosine kinase (SRC)-family and protein kinase C (PKC) inhibitors, and was resistant to inhibitors of protein kinase A (PKA) and metalloproteinases. AREG also induced the rapid activation of MAPK3/1 in cumulus cells, but this activation was only dependent on the EGFR TK activity. We conclude that in cumulus cells, FSH induces a rapid activation of MAPK3/1 by the ligand-independent transactivation of EGFR, requiring SRC and PKC activities. This rapid activation of MAPK3/1 precedes the second mechanism participating in the generation and maintenance of active MAPK3/1-the ligand-dependent activation of EGFR depending on the synthesis of EGF-like peptides.
Keywords: amfiregulin; Animals; Female; ErbB Receptors; erbB receptory; epidermal growth factor receptor; IVM techniky; ženské pohlaví; Follicle Stimulating Hormone; signal transduction; mitogenem aktivovaná proteinkinasa 3; Oocytes; Transcriptional Activation; amphiregulin; mitogenem aktivovaná proteinkinasa 1; oocyty; prasata; FSH; signální transdukce; kultivované buňky; Signal Transduction; In Vitro Oocyte Maturation Techniques; mitogen-activated protein kinase 3/1; Cells, Cultured; Cumulus Cells; Swine; skupina kinas odvozených od src-genu; kumulární buňky; Mitogen-Activated Protein Kinase 3; aktivace transkripce; cumulus cells; src-Family Kinases; zvířata; Mitogen-Activated Protein Kinase 1; extracelulárním signálem regulované MAP kinasy; Amphiregulin; folikuly stimulující hormon; Extracellular Signal-Regulated MAP Kinases